Penentuan Harga Pokok Produksi Pada UMKM Home Industri di Kabupaten Kutai Timur - Yazid Bustomi, Muhamad; Rusmiyati, Rusmiyati; Suryanto, Joko; Novita Dewi, Indah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
One indicator of the competitiveness of micro, small, and medium enterprises (MSMEs) was the production process with standard operating procedures. The production process in the home industry business requires good management, including of calculating the production costs. The objectives in this community service were (1) to provide an understanding of the importance of calculating the production cost as a basic for MSMEs in determining the selling price products. (2) to explain the calculation of the production cost for MSMEs as one of strategy in marketing the resulting products. This community service activity was carried out to the home industry MSMEs of LPB Pabanet Partners with the counseling and the presentation method, followed by discussions about the process of determining the production cost related to the business by each MSMEs. The home industry MSMEs participants to be able to take part in the activities well, seemed enthusiastic participants in discussions regarding the calculation of the production cost of businesses by each MSMEs. Through this activity, hoped that the home industry MSMEs could apply calculations for each resulting product in order to determine the selling price product correctly so getting profits with the expectations of MSMEs